3 - Crise et Recul du Nationalisme Economique d’etat Collectif en Afrique: by Bernard Founou-Tchuigoua - Bernard Founou-Tchuigoua (Africa Development, 1988)
When the Ο AU adopted the Lagos Plan of Action in 1980 it implicitly admitted that the nationalist movement was right in ascribing the under-development of the continent to imperialism and in advocating delinking as Samir Amin calls it - as a (necessary but of course insufficient) requirement for development; better still the OAU rejected the counter Plan (Berg Report) drafted by the World Bank. In 1986, however, with the adoption of Africa's Priority Programme for Economic Recovery (APPER) the OAU shifted to the position imposed by the World Bank and the IMF. In effect APPER rejects the principle of self-centered development even that of food self sufficiency; advocates a tightening of rela tions between Africa and the Center and legitimizes structural adjustment, these policy changes mark an ideological shift from nationalism toe neo-liberalism. The vulgar anti socialism of political leaders including a few who claim to be Marxist is at the root of externally induced corruption and political oppression. In the main, African national liberation movements have failed to inculcate a democratic tradition. Thus democracy has to play a leading role in the search for alternatives. Marxism should be a component of such a democracy - a type of Marxism which must stop short of imposing one school of thought one which does not have claim to a monopoly of truth.